Chemotaxis assay for evaluation of memory-like behavior in wild-type and Alzheimer's-disease-like C. elegans models - Cao, Shu-Qin; Wang, He-Ling; Palikaras, Konstantinos; Tavernarakis, Nektarios; Fang, Evandro Fei (STAR protocols, 2023)
Here, we present an olfactory-dependent chemotaxis assay for evaluating changes in memory-like behavior in both wild-type and Alzheimer's-disease-like C. elegans models. We describe steps for synchronizing and preparing C. elegans populations and for performing isoamyl alcohol conditioning during starvation and chemotaxis assaying. We then detail counting and quantification procedures. This protocol is applicable to mechanistic exploration and drug screening in neurodegenerative diseases and brain aging.
Keywords: Molecular Biology; neuroscience